Cytokine Hemoadsorption as Rescue Therapy for Critically Ill Patients With SARS-CoV-2 Pneumonia With Severe Respiratory Failure and Hypercytokinemia - Ruiz-Rodríguez, Juan Carlos; Chiscano-Camón, Luis; Ruiz-Sanmartin, Adolf; Palmada, Clara; Paola Plata-Menchaca, Erika; Franco-Jarava, Clara; Pérez-Carrasco, Marcos; Hernández-González, Manuel; Ferrer, Ricard (Frontiers in Medicine, 2022)
Introduction: A dysregulated inflammatory response, known as “cytokine storm”, plays an important role in the pathophysiology of coronavirus 2019 disease (COVID-19). Identifying patients with a dysregulated inflammatory response and at high risk for severe respiratory failure, organ dysfunction, and death is clinically relevant, as they could benefit from the specific therapies, such as cytokine removal by hemoadsorption. This study aimed to evaluate cytokine hemoadsorption as rescue therapy in critically ill patients with SARS-CoV-2 pneumonia, severe respiratory failure refractory to prone positioning, and hypercytokinemia. Methods: In this single center, observational and retrospective study, critically ill patients with SARS-CoV-2 pneumonia, severe acute respiratory failure, and hypercytokinemia were analyzed. All the patients underwent cytokine hemoadsorption using CytoSorb® (Cytosorbents Europe, Berlin, Germany). The indication for treatment was acute respiratory failure, inadequate clinical response to the prone position, and hypercytokinemia. Results: Among a total of 343 patients who were admitted to the intensive care unit (ICU) due to SARS-CoV-2 infection between March 3, 2020 and June 22, 2020, six patients received rescue therapy with cytokine hemoadsorption. All the patients needed invasive mechanical ventilation and prone positioning. A significant difference was found in the pre- and post-treatment D-dimer (17,868 mcg/ml [4,196–45,287] vs. 4,488 mcg/ml [3,166–17,076], p = 0.046), C-reactive protein (12.9 mg/dl [10.6] vs. 3.5 mg/dl [2.8], p = 0.028), ferritin (1,539 mcg/L [764–27,414] vs. 1,197 ng/ml [524–3,857], p = 0.04) and interleukin-6 (17,367 pg/ml [4,539–22,532] vs. 2,403 pg/ml [917–3,724], p = 0.043) levels. No significant differences in the pre- and post-treatment interleukin-10 levels (22.3 pg/ml [19.2–191] vs. 5.6 pg/ml [5.2–36.6], p = 0.068) were observed. Improvements in oxygenation (prehemoadsorption PaO2/FIO2 ratio 103 [18.4] vs. posthemoadsorption PaO2/FIO2 ratio 222 [20.9], p = 0.029) and in the organ dysfunction (prehemoadsorption SOFA score 9 [4.75] vs. posthemoadsorption SOFA score 7.7 [5.4], p = 0.046) were observed. ICU and in-hospital mortality was 33.7%. Conclusions: In this case series, critically ill patients with COVID-19 with severe acute respiratory failure refractory to prone positioning and hypercytokinemia who received adjuvant treatment with cytokine hemoadsorption showed a significant reduction in IL-6 plasma levels and other inflammatory biomarkers. Improvements in oxygenation and SOFA score were also observed.